Effect of Matrix Rhythm therapy and IFT on OA knee - Palekar, Pramod J; Baxi, Gaurang; Palekar, Tushar J. (Journal of Neonatal Surgery, 2025)
Osteoarthritis of the knee (OA) is a widespread degenerative joint disease that can be described as the degradation of cartilage and inflammation, pain, and poor functioning of the knee. The growing rate of OA especially on the elderly populations requires the need to consider suitable non-pharmacological intervention. The present study aims at investigating the comparative effectiveness of the Matrix Rhythm Therapy (MRT), and Interferential Therapy (IFT) in pain reduction and joint functional improvement in patients with knee OA. The group of 40 participants with moderate-grade knee OA was randomly chosen and separated into two equal groups (receiving MRT and IFT) and exposed to the session of four weeks. The Viulalogue Analogue Scale (VAS) was taking to measure pain and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) was used to gauge functional mobility. The findings showed that both subgroups elicited significant improvement in the outcome of patients, with a little better effect being observed in MRT in terms of pain and mobility of the patient. These observations are indications that there is possibility of MRT replacing or becoming a complement of conventional electrotherapy in the conservative management of OA knee.